Long-term effect of curcuminoid treatment on resin-to-dentin bond strength - Atay Meltem Tekbas; Seseogullari-Dirihan Roda; Mutluay Mustafa Murat; Tezvergil-Mutluay Arzu (Wiley, 2025)
Endogenous dentin proteases contribute to the degradation of collagen fibrils in the hybrid layer. Recently, inhibition of host-derived proteases by curcuminoids has shown promising results. The aim of this study was to evaluate the effect of curcuminoid treatment on the microtensile bond strength (μTBS) after 24 h or 12 months of storage. Fifty-four extracted sound human molars were flattened to mid-coronal dentin and divided into nine groups. After phosphoric acid-etching for 15 s, the dentin was experimentally treated for 60 s using 100 μM or 200 μM of curcumin, diflourobenzocurcumin, or demethoxycurcumin dissolved in 1% and 2% dimethyl sulfoxide (DMSO)/water solutions. Untreated and DMSO-treated groups served as controls. After bonding agent application, each tooth was restored with dental composite. The molars were sectioned into 0.9 × 0.9 × 6 mm beams. The μTBS testing was performed after 24 h and 12 months of storage in artificial saliva. Data were analyzed using regression analyses. Failure patterns were evaluated using scanning electron microscopy. Dentin treatment with curcuminoids did not adversely affect 24-h μTBS compared to controls. After 12 months, the μTBS of curcuminoid groups was statistically significantly higher than the controls. This study indicates the feasibility of using curcuminoids as protease inhibitors.